Noninvasive Ventilation in the Treatment of Severe Community-Acquired Pneumonia: The Experience of a Single Center. Issue 4 (July 2015) - Perazzo, Alessandro; Gatto, Piergiorgio; Colamartino, Simona; Torreggiani, Tullio; Barlascini, Cornelius; Nicolini, Antonello
Abstract : Background: Treatment of severe community-acquired pneumonia (CAP) includes antibiotic therapy as well as hemodynamic and ventilatory support. The use of invasive ventilation may be associated with greater acute morbidity. For this reason, noninvasive ventilation (NIV) has been used for acute respiratory failure (ARF) to avoid endotracheal intubation. However, few studies have assessed the efficacy of NIV in patients with pneumonia. Noninvasive ventilation usefulness is not clear in severe CAP. There is greater variability in NIV failure in CAP than in other pulmonary diagnoses. Methods: We prospectively assessed 65 patients with CAP and severe ARF (PaO2 /FIO2, ⩽250); 28 had de novo ARF and 37 had previous cardiac or respiratory disease. We assessed predictors of NIV failure and hospital mortality in univariate and multivariate analyses. Results: Noninvasive ventilation failed in 13 (20.0%) patients with de novo ARF. Failure rates for patients with previous cardiac or respiratory disease (17.8% and 21.6%) were similar. A higher chest x-ray score at admission, a higher heart rate after 1 hour of NIV, and a higher alveolar-arterial gradient after 24 hours of NIV independently predicted NIV failure. Conclusions: Noninvasive ventilation success is related to a strict selection and monitoring of patients. Similar NIV-failure rates were observed in patients with de novo and previous cardiac or respiratory disease. There are clinical parameters that predict NIV failure and mortality.